Phenylpropanoid and lignan glycosides from the aerial parts of Lespedeza cuneata. (January 2016) - Zhou, Jian; Li, Chuang-Jun; Yang, Jing-Zhi; Ma, Jie; Wu, Lian-Qiu; Wang, Wen-Jie; Zhang, Dong-Ming
Graphical abstract: Four phenylpropanoid glucosides (1 –4 ) and five lignan glycosides (5 –9 ) were isolated from the aerial parts of Lespedeza cuneata, together with three known lignan glycosides (10 –12 ). Compounds4, 5, 7, 9, 10, and12 could activate the transcription of xbp1 to varying degrees, with EC50 values ranging from 0.18 to 0.64 μM. Highlights: Four phenylpropanoid glucosides and five lignan glycosides were isolated from Lespedeza cuneata . Their structures and absolute configurations were established from NMR and CD data. Anti-ulcerative colitis activity was evaluated by dual luciferase report gene assay targeting xbp1 . Abstract: Four phenylpropanoid glucosides (1 –4 ) and five lignan glycosides (5 –9 ) were isolated from the aerial parts of Lespedeza cuneata, together with three known lignan glycosides (10 –12 ). Their structures were elucidated on the basis of spectroscopic analyses, and the absolute configurations of compounds5 –9 were determined from the CD spectra. In addition, the compounds were tested for their ability to activate the transcription effect on xbp1 promoter. Compounds4, 5, 7, 9, 10, and12 could activate the transcription of xbp1 to varying degrees, with EC50 values ranging from 0.18 to 0.64 μM.